2017
DOI: 10.4103/iju.iju_372_16
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone versus clomiphene citrate in managing symptoms of hypogonadism in men

Abstract: Introduction:Both clomiphene citrate (CC) and testosterone supplementation therapy (TST) are effective treatments for men with hypogonadism. We sought to compare changes in symptoms and treatment efficacy in hypogonadal men before and after receiving CC and TST.Patients and Methods:52 men who received TST and 23 men who received CC for symptomatic hypogonadism were prospectively followed for change in hormone levels and symptoms after treatment. These men were also compared to eugonadal men who were not on CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Anastrazole, an aromatase inhibitor, is also employed to increase T levels and is beneficial for spermatogenesis if the serum T to estrogen ratio is < 10 (41, 42). While these medications are efficacious, using them for male hypogonadism treatment is considered off-label by the Food and Drug administration and carry side effects of decreased bone mineral density and libido (42).…”
Section: Treatment Options For Adolescent and Young Adulthood Men With mentioning
confidence: 99%
“…Anastrazole, an aromatase inhibitor, is also employed to increase T levels and is beneficial for spermatogenesis if the serum T to estrogen ratio is < 10 (41, 42). While these medications are efficacious, using them for male hypogonadism treatment is considered off-label by the Food and Drug administration and carry side effects of decreased bone mineral density and libido (42).…”
Section: Treatment Options For Adolescent and Young Adulthood Men With mentioning
confidence: 99%
“…The qADAM score also had a positive correlation with total testosterone and with SHIM scores. 44 Dadhich et al 45 evaluated changes in hypogonadal symptoms after 3 months of receiving CC or TRT, and observed a significant improvement in qADAM scores in both the CC and TRT group. Investigators, through a randomized controlled study, also reported that CC and human chorionic gonadotropin therapy both improved qADAM score when these treatment regimens were used separately or as a combination.…”
Section: Use For Men With Hypogonadismmentioning
confidence: 99%
“…Clomiphene citrate has been demonstrated to increase testosterone but also improve hypogonadal symptoms 69, 70 . However, one study indicated that the use of clomiphene citrate is less effective than TRT at increasing serum testosterone levels and improving hypogonadal symptoms and libido 71 . Enclomiphene citrate is a shorter-acting preparation of clomiphene citrate that has been shown to improve sperm counts but also testosterone levels equivalent to exogenous testosterone 72 .…”
Section: Selective Oestrogen Receptor Modulatorsmentioning
confidence: 99%